THE DEVELOPMENT PROCESS OF THE SARONG WOVEN FROM THE PAST UNTIL NOW (Karya Ilmiah Mahasiswa (KIMA), 2023)
The goal of this research was to determine the evolution of a culture that is frequently employed at traditional ceremonies and weddings. This study employs qualitative description to explain the elements that contribute to the survival of the craft and culture of woven sarongs in Sengkang. This is a descriptive study with a qualitative analysis methodology that is certain to directly define the research findings collected in the field as they are. The findings of this study are based on the history of past sarong weaving cultures, and they reveal that the majority of people in Sengkang, Wajo Regency, wear a handmade sarong as an obligation at every important traditional event and wedding. On every occasion, they regard the weaved sarong to be their identity. Silk sarongs have been one of Wajo's major items. They work in the silk textile industry to support themselves and their families.